KERAJAAN ALLAH DALAM INJIL LUKAS - Neni Sintani; Nesti Tirtasari; Sarmauli (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
This study aims to examine in depth the concept of the Kingdom of God in the Gospel of Luke and its relevance to contemporary life. The main issue discussed is how the meaning of the Kingdom of God is understood in the Gospel of Luke and how this concept can be applied in the context of modern life. This study uses a qualitative approach with a literature review method, by examining various relevant theological sources. The results of the study show that the Kingdom of God in the Gospel of Luke is not understood as a kingdom in a physical or political sense, but as the real work of God present in human history through Jesus Christ. The term Basileia tou Theou emphasizes the active and dynamic reign of God. This Kingdom is characterized by its concern for the poor, the values of love and forgiveness, and its universal nature. In addition, the Kingdom of God has both a present and a future dimension. In the context of contemporary life, the values of the Kingdom of God can be realized through social concern, economic empowerment, attention to mental health, and responsibility toward the environment. Thus, the Kingdom of God is not only a theological concept, but also a reality that must be lived out in everyday life.